New Ru-3(CO)(12) derivatives with bulky diphosphine ligands: synthesis, structure and catalytic potential for olefin hydroformylation - Diz, Enrique Lozano; Neels, Antonia; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 2001)
The diphosphine clusters Ru-3(CO)(10)(dcpm) (1) and Ru-3(CO)(10)(F-dppe) (2) as well as the bis(diphosphine) clusters Ru-3(CO)(8)(dcpm)(2) (3) and Ru-3(CO)(8)(F-dppe)(2) (4) have been synthesised from Ru-3(CO)(12) and the bulky diphosphines 1,2-bis[bis(pentafluorophenyl)phosphino]ethane (F-dppe) and bis(dicyclohexylphosphino)methane (dcpm). While the single-crystal X-ray structure analyses of 1, 2 and 3 show the expected mu (2)-eta (2) coordination of the diphosphine ligands, that of 4 reveals an unusual structure with one mu (2)-eta (2)-diphosphine and one mu (1)-eta (2)-diphosphine ligand. The clusters 1-4 catalyse the hydroformylation of ethylene and propylene to give the corresponding aldehydes, 2 showing higher activities than those observed for Ru-3(CO)(12) and Ru-3(CO)(10)(dppc). (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: ruthenium; carbonyl; clusters; diphosphine; hydroformylation; CARBONYL DERIVATIVES; PHOSPHORUS LIGANDS; CLUSTER CHEMISTRY; CRYSTAL-STRUCTURE; TRIRUTHENIUM; RU3(CO)12; PHOSPHINES; BINUCLEAR; ROUTE